Carotenoid functions and other isoprenoids in plants - Gantt, Elisabeth (Henry Stewart Talks, 2007)
Carotenoids in the diet, Vision, Isoprenoids to carotenoid biosynthesis, Photosynthetic apparatus, Requirement of vital carotenoids, Eco-physiology, Light harvesting carotenoids, Bioengineering of dietary additives, Beta-carotene and ketocarotenoids